The applicability of Demirjian’s and Nolla’s dental age estimation methods for children in Surabaya, Indonesia (Bulletin of the International Association for Paleodontology, 2025)
Accurate age estimation in children is crucial in various justice-related contexts, including adoption, asylum claims, and immigration cases. Additionally, dental age estimation plays a key role in treatment planning within pediatric dentistry and orthodontics. This study aimed to assess the applicability of two widely used dental age estimation methods, Demirjian and Nolla, for children aged 6 to 15 years in Surabaya, Indonesia. A total of 200 panoramic radiographs from the Dental Hospital, Universitas Airlangga were analyzed to compare chronological age (CA) and estimated dental age (DA). The results revealed significant differences between CA and DA when using the Demirjian method for males (p